(untitled) (International Journal of Engineering and Computer Science, 2017)
The structural design addresses the issues of keyword based image retrieval and content-based image retrieval through the use of qualitative spatial representations over semantic image annotations. Three types of image retrievalSemantic Retrieval based on Global Labels of Images,Semantic Retrieval based on Image concepts, Semantic Retrieval based on Qualitative Relations